Antecedents of Continued Use Intention in the Era of Data Breaches: An Empirical Study of Pakistani Online Banking Users - Malik, Momena (My University, 2020)
Data breaches are a rising threat to the banking sector in which the customer’s information is accessed by unauthorized persons leading to reduced trust and reputation. The reduction in trust and satisfaction may result in discontinuation of online banking services. The purpose of this study is to: 1) identify the factors that affect the intention to continue use of online banking, and 2) to determine the effects data breach incidents on continued usage and its relevant antecedents. A model was developed based on Expectation Confirmation Model and Technology Acceptance Model with integrating factors of trust, perceived risk, satisfaction, perceived security and privacy. To test the model, data was collected using online survey from 103 Pakistan online banking users, which were hard to reach population in Pakistan. The findings of the model showed that trust and satisfaction are primary predictors of intention to continue use. Perceived usefulness and expectancy confirmation significantly impacted satisfaction, whereas, expectancy confirmation and perceived security had a significant impact on trust. It was also found that user’s perception of security and privacy, their trust beliefs, their satisfaction levels and their intention to continue use online banking service were negatively affected post the data breach news. The research has practical implications for the banking industry to create solutions to attain secure internet banking and also help them to increase customer trust and continued usage of online banking technology. It also highlights the need for banks to notify their customers about data breaches and the steps taken to mitigate them.
Keywords: Online banking, Data breach, Perceived security and privacy, Trust, Satisfaction, Continuance Intention